Removal of Hexavalent Chromium from Waste Water Using Newly Developed Activated Carbon from Bark of Butea monosperma - Hunge, S. S. (Current Overview on Science and Technology Research Vol. 6, 2022)
The presence of heavy metals in aquatic systems has developed into a significant issue. The development of novel methods for the removal of heavy metal ions from contaminated water has received a lot of attention as a result. One of the most efficient technologies for removing harmful heavy metal ions is the adsorption technique. Metals that are toxic to human beings and ecological environments include copper, chromium, lead, mercury, cadmium, nickel, iron, and cobalt. One of the main metal ions that pollute the environment is hexavalent chromium, which is found in wastewater from the majority of different industrial sectors. For the elimination of hexavalent chromium, a number of traditional physical and chemical treatment procedures have been published in the literature. However, these procedures are costly, energy-intensive, and produce by-products that are toxic and carcinogenic. In a recent study, the effectiveness of activated carbon made from Butea monosperma bark in removing Cr(VI) from contaminated water was examined in relation to many parameters, including the impact of pH, the dosage of the adsorbent, the contact time, and the starting metal ion concentration. The optimal pH level, equilibrium pH=6.5, was required for hexavalent chromium uptake. With increasing contact duration, Cr(VI) removal from aqueous solution increases, and equilibrium was reached after 150 minutes. Additionally, there was an increase in Cr(VI) removal with an increase in adsorbent dosage. The maximum adsorption of Cr(VI) (96%) was examined at 5.0 g/l of adsorbent dose. The upsurge in the initial concentration of Cr(VI) decreases the percent removal of Cr(VI). This investigation established that the freshly created activated carbon from the bark of Butea monosperma may be employed as a successful adsorbent to remove hexavalent chromium from aqueous solution that is both less expensive and energy-intensive.